(untitled) (Chittagong University Journal of Biological Sciences, 2025)
Tomato (Lycopersicon esculentum (L.) Mill.) production relies heavily on nutrient availability, which significantly influences plant growth, yield, and fruit quality. With rising demand for sustainable agriculture, poultry manure biogas residues (PMBR) are gaining attention as alternatives or supplements to synthetic fertilizers. This study assessed the effects of PMBR compared to conventional fertilizers (NPK) under field conditions using a randomized complete block design with six treatments: sole PMBR (20 ton ha⁻¹), sole NPK (100% RDF: 135 kg N ha⁻¹, 45 kg P ha⁻¹, 75 kg K ha⁻¹), and combined PMBR–NPK applications (15 ton ha⁻¹ PMBR + 25% RDF, 10 ton ha⁻¹ PMBR + 50% RDF, 5 ton ha⁻¹ PMBR + 75% RDF). Growth parameters (leaves, height, branches) and yield parameters (fruit number, weight, total yield) were measured. Results showed integrated PMBR–NPK treatments achieved the highest yields, while sole PMBR maintained comparable performance with reduced inputs, highlighting PMBR’s potential as an eco-friendly, cost-effective nutrient source. Chittagong Univ. J. B. Sci. Vol. 13 (1&2): 12-22, 2025